Analysis of Intertextuality on Short Stories Entitled Hanya Isyarat by Dewi Lestari and Love by Guy De Maupassant - Miza Rahmatika Aini; Febby Cahyani (JOSAR (Journal of Students Academic Research), 2023)
This study, which was conducted by two researchers, had the objective of analyzing the intertextuality of the short story literary works "Only Cue" by Dewi Lestari and "Love" by Guy De Maupassant. The research was conducted using a qualitative descriptive method with content analysis and literature study. The data in this study were obtained from data relevant to the problem or topic under study by conducting literature studies from several sources, for example research journals with several previous studies. The results of the study show that there are similarities in the themes and messages conveyed by the author, namely about love and sacrifice, although there are differences in the depiction of the characters in the story. The plot of the story also has differences, "Just a hint" uses a progressive plot while "Love" uses a "flashback" plot